Stepwise emergence of CO gas sensing response and selectivity on SnO2 using C supports and PtOx decoration - Kim, Yong Hwan; Lee, Seung Yong; Ji, Yunseong; Lee, Jeong Ho; Kim, Dae Woo; Lee, Byeongdeok; Jin, Changhyun; Lee, Kyu Hyoung (Frontiers in Chemistry, 2024)
Room temperature gas sensing is crucial for practical devices used in indoor environments. Among various materials, metal oxides are commonly used for gas sensing, but their strong insulating properties limit their effectiveness at room temperature. To address this issue, many studies have explored diverse methods such as nanoparticle decoration or conductive support, etc. Here, we report the emergence of gas-sensing functionality at room temperature with improved CO gas selectivity on SnO2 nanoparticles through sequential steps by using amorphous carbon (a-C) support and PtOx decoration. The SnO2 decorated on amorphous carbon shows enhanced gas adsorption compared to inactive gas sensing on SnO2 decorated carbon support. The higher Vo site of SnO2 on a-C induces gas adsorption sites, which are related to the higher sp 2 bonding caused by the large density of C defects. The ambiguous gas selectivity of SnO2/a-C is tailored by PtOx decoration, which exhibits 6 values of sensing responses (Rg/Ra or Ra/Rg) under CO gas at room temperature with higher selectivity. Compared to PtOx/a-C, which shows no response, the enhanced CO gas sensing functionality is attributed to the CO adsorption site on PtOx-decorated SnO2 particles. This report not only demonstrates the applicability of CO gas sensing at room temperature but also suggests a strategy for using SnO2 and carbon compositions in gas sensing devices.